THE ROLE OF USED BAGS AS A CONTAINER IN INFLUENCING THE IMPROVEMENT OF WASTE SEGREGATION IN PENATAHAN VILLAGE - Anggreni, Dewi; Chandra Mandira, I Made; Kumalasari, Erni; Lisa Marlina, Ni Kadek; Triskananda Sidartha, Ketut Wisnu (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The problem taken in the Service Program for the Penatahan village community through the 2022 Real Work Lecture is to increase public awareness about the importance of keeping the environment clean. The Service Program for the Penatahan Village community that we carried out starting from January 10 to February 9 2022 with the offline method. The benefits of this Service Program for us are gaining experience in applying the knowledge gained in higher education and collaborating with the community or certain communities. This Service Program aims to help the Penatahan Village community to reduce scattered waste by carrying out waste collection activities to create a clean environment. The waste problem that occurs in Penatahan Village is caused by the government not having built a garbage disposal site so that there is no place to accommodate garbage originating from households which causes a buildup of garbage. If the accumulated waste is not treated properly, it will cause environmental pollution, which will have an impact on health. After discussing, the work program carried out was that we gave garbage sacks to the people of Penatahan Village as a substitute for trash bins and then sorted the collected waste, which would later be processed into crafts as a form of implementation and solution to the waste problems in Penatahan Village.